(untitled) (Global Journal of Medical Research, 2018)
Aqueous extract of Moringaolifera (Lam) was evaluated for protective and antioxidant activities in rats. The plant extract showed a remarkable chemo-protective activity on nicotine induced liver toxicity as judged by serum maker enzyme and some antioxidant levels in the liver of male albino rats weighing between 180 and 200g. The animals were grouped into five of six rats each which were intraperitoneally induced with nicotine at 1mg/kg body weight except the control group. Some biochemical parameters (Aspartate aminotransferase (AST), Alanineaminotransferase (ALT), alkaline phosphatase (ALP), creatinine kinase malondialdehyde (MDA)); some antioxidant indices and lipid profiles were monitored. Induction of nicotine produced a significant increase in the level of malondialdehyde and decrease in the levels of superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH) as compared to the control animals. Treatment with aqueous extract of Moringaoleifera leaf was found to produce a significant decrease in TBARS and increase in GSH, SOD and CAT in the plasma and liver homogenate of the nicotine induced rats. The levels of total cholesterol, triglycerides, HDL-cholesterol and LDL-cholesterol in plasma and hepatic tissues of the experimental animals were also monitored. Significant protection was seen in the extract and standard drug (Lisinopril) treated nicotine induced animals. Administration of aqueous extract of the plant brings about a significant restoration towards the control values.